2002
DOI: 10.1002/ccd.10139
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique for stent delivery in tortuous coronary arteries: Report of three cases

Abstract: We present a novel technique for stent delivery across tortuous lesions. Gentle forward pressure was applied on the stent balloon while the balloon was inflated to 2-3 atm. This resulted in the balloon and stent crossing the impeding segment and settling in the target site where it was deployed with excellent angiographic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Fernandes et al [27] reported three cases of stent angioplasty on angulated lesions, and found that arterial bends or sharp vessel angulation can obstruct the passage of the stent. Myouchin et al [28] studied 31 cases of stent deployment close to inflection points of the artery, of which 2 had unsuccessful treatment of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al [27] reported three cases of stent angioplasty on angulated lesions, and found that arterial bends or sharp vessel angulation can obstruct the passage of the stent. Myouchin et al [28] studied 31 cases of stent deployment close to inflection points of the artery, of which 2 had unsuccessful treatment of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that nearly 5% of lesions could not be successfully treated with dug‐eluting stents [6]. For cases involving severe calcification or tortuosity of the proximal section that hinders stent delivery, methods such as using a wire with high backup force that extends the vessel, inner catheter, anchor techniques, and aspiration catheter were attempted in many cases [7–10]. Buddy and extra support wire, inner catheter, and anchor technique enable the stent delivery to provide not only the guiding catheter with coaxial positioning but also higher backup support.…”
Section: Discussionmentioning
confidence: 99%
“…The deliverability of a coronary stent is usually assessed by how easy it is to navigate through tortuous/calcified vasculature to the target lesion and cross the lesion. Optimal support by guiding catheters, adequate lesion preparation, and use of buddy wires/stiffer wires has been suggested to facilitate stent delivery in these complex lesion subsets . The GuideLiner catheter (Vascular Solutions, Inc., Minneapolis, MN, USA) is also a useful adjunctive tool to facilitate stent delivery across heavily calcified lesions and/or tortuous vessels .…”
Section: Introductionmentioning
confidence: 99%